Fungal diversity notes 709–839: taxonomic and phylogenetic contributions to fungal taxa with an emphasis on fungi on Rosaceae - Dhanushka N. Wanasinghe (2018)
© 2018, School of Science. This paper is the seventh in the Fungal Diversity Notes series, where 131 taxa accommodated in 28 families are mainly described from Rosa (Rosaceae) and a few other hosts. Novel fungal taxa are described in the present study, including 17 new genera, 93 new species, four combinations, a sexual record for a species and new host records for 16 species. Bhatiellae, Cycasicola, Dactylidina, Embarria, Hawksworthiana, Italica, Melanocucurbitaria, Melanodiplodia, Monoseptella, Uzbekistanica, Neoconiothyrium, Neopaucispora, Pararoussoella, Paraxylaria, Marjia, Sporormurispora and Xenomassariosphaeria are introduced as new ascomycete genera. We also introduce the new species Absidia jindoensis, Alternaria doliconidium, A. hampshirensis, Angustimassarina rosarum, Astragalicola vasilyevae, Backusella locustae, Bartalinia rosicola, Bhatiellae rosae, Broomella rosae, Castanediella camelliae, Coelodictyosporium rosarum, Comoclathris rosae, C. rosarum, Comoclathris rosigena, Coniochaeta baysunika, C. rosae, Cycasicola goaensis, Dactylidina shoemakeri, Dematiopleospora donetzica, D. rosicola, D. salsolae, Diaporthe rosae, D. rosicola, Endoconidioma rosae-hissaricae, Epicoccum rosae, Hawksworthiana clematidicola, H. lonicerae, Italica achilleae, Keissleriella phragmiticola, K. rosacearum, K. rosae, K. rosarum, Lophiostoma rosae, Marjia tianschanica, M. uzbekistanica, Melanocucurbitaria uzbekistanica, Melanodiplodia tianschanica, Monoseptella rosae, Mucor fluvius, Muriformistrickeria rosae, Murilentithecium rosae, Neoascochyta rosicola, Neoconiothyrium rosae, Neopaucispora rosaecae, Neosetophoma rosarum, N. rosae, N. rosigena, Neostagonospora artemisiae, Ophiobolus artemisiicola, Paraconiothyrium rosae, Paraphaeosphaeria rosae, P. rosicola, Pararoussoella rosarum, Parathyridaria rosae, Paraxylaria rosacearum, Penicillium acidum, P. aquaticum, Phragmocamarosporium rosae, Pleospora rosae, P. rosae-caninae, Poaceicola agrostina, P. arundinicola, P. rosae, Populocrescentia ammophilae, P. rosae, Pseudocamarosporium pteleae, P. ulmi-minoris, Pseudocercospora rosae, Pseudopithomyces rosae, Pseudostrickeria rosae, Sclerostagonospora lathyri, S. rosae, S. rosicola, Seimatosporium rosigenum, S. rosicola, Seiridium rosarum, Setoseptoria arundelensis, S. englandensis, S. lulworthcovensis, Sigarispora agrostidis, S. caryophyllacearum, S. junci, S. medicaginicola, S. rosicola, S. scrophulariae, S. thymi, Sporormurispora atraphaxidis, S. pruni, Suttonomyces rosae, Umbelopsis sinsidoensis, Uzbekistanica rosae-hissaricae, U. yakutkhanika, Wojnowicia rosicola, Xenomassariosphaeria rosae. New host records are provided for Amandinea punctata, Angustimassarina quercicola, Diaporthe rhusicola, D. eres, D. foeniculina, D. rudis, Diplodia seriata, Dothiorella iberica, Lasiodiplodia theobromae, Lecidella elaeochroma, Muriformistrickeria rubi, Neofusicoccum australe, Paraphaeosphaeria michotii, Pleurophoma pleurospora, Sigarispora caulium and Teichospora rubriostiolata. The new combinations are Dactylidina dactylidis (=Allophaeosphaeria dactylidis), Embarria clematidis (=Allophaeosphaeria clematidis), Hawksworthiana alliariae (=Dematiopleospora alliariae) and Italica luzulae (=Dematiopleospora luzulae). This study also provides some insights into the diversity of fungi on Rosa species and especially those on Rosa spines that resulted in the characterisation of eight new genera, 45 new species, and nine new host records. We also collected taxa from Rosa stems and there was 31% (20/65) overlap with taxa found on stems with that on spines. Because of the limited and non-targeted sampling for comparison with collections from spines and stems of the same host and location, it is not possible to say that the fungi on spines of Rosa differ from those on stems. The study however, does illustrate how spines are interesting substrates with high fungal biodiversity. This may be because of their hard structure resulting in slow decay and hence are suitable substrates leading to fungal colonisation. All data presented herein are based on morphological examination of specimens, coupled with phylogenetic sequence data to better integrate taxa into appropriate taxonomic ranks and infer their evolutionary relationships.